2019
DOI: 10.5334/aogh.2350
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Risk Factors for Type 2 Diabetes among Arabs in Israel

Abstract: Background: Type 2 Diabetes Mellitus (T2DM) is becoming increasingly prevalent and is considered to be a major public health threat worldwide. Behavioral and sociodemographic factors associated with T2DM vary within different societies. Objective: The aim of this study is to determine the various behavioral and sociodemographic factors associated with T2DM in the Arab society in Israel. Methods: A cross-sectional study was conducted based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“… 19 An Israeli study showed that 13.7 % of the 1,894 respondents in an Arab community aged 21 years and above had T2DM. 8 This result was lower than the study in Saudi Arabia, where 25.1% of the 872 respondents had T2DM. 20 Thus, the increasing prevalence of T2DM, particularly UDD, requires more intensive prevention efforts by early identification of the risk factors.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“… 19 An Israeli study showed that 13.7 % of the 1,894 respondents in an Arab community aged 21 years and above had T2DM. 8 This result was lower than the study in Saudi Arabia, where 25.1% of the 872 respondents had T2DM. 20 Thus, the increasing prevalence of T2DM, particularly UDD, requires more intensive prevention efforts by early identification of the risk factors.…”
Section: Discussionmentioning
confidence: 60%
“…The results indicate that the risk factors for T2DM are generally similar across the different ethnic groups with age, family history of DM, obesity and hypertension as the most common. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of DM is influenced by demographic and socioeconomic profiles. According to Sharkia et al, [10] the educational qualification and income levels may affect increasing the prevalence of T2DM in Israel. According to Walker et al, [6] age-specific life expectancy was calculated based on stratified socioeconomic status for T2DM patients in Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…Sharkia et al reported that education and income levels might have an increasing effect on the prevalence of T2DM in Israel. [10] Not only in Israel, but several studies are also available that confirm the demographic and socioeconomic influence on the prevalence of DM. [11][12][13][14] Disease awareness particularly on DM has an extraordinary effect as a positive influence to prevent the disease and its comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the causes include obesity, family history, inactivity, education and income. Studies have pointed out that T2DM is a result of a combination of sociodemographic factors and health behaviors [ 45 ]. Additionally, it was reported that greater risk of diabetes among Arabs were due to lifestyle factors, family history of diabetes and, among women, history of gestational diabetes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%